BEING A FOOTBALL FAN, IDENTIFICATION AND IDENTITY: FROM BEING A FAN TO FANATICISM - Mert Kerem Zelyurt (ümit doğan üstün, 2019)
Football is not only the most popular sport all around the world but also the most common one among sports. With the number of the players, followers and fans, and the interest of people of all ages, football is clearly ahead of other sports branches. The social aspects of football such as being a fan, play, pleasure etc. has let the game to become a part of the society and daily life. Besides, being multidimensional has let the football become an identification area. It is an important matter of today that individuals can easily change their preferences in daily life (political party etc.) easily even if they fail however, it is not a subject matter for their football teams. Being a fan of a football team can respond to the spiritual, spiritual and social needs of an individual beyond being a sporting activity. In this study, it has been problematized that football is a social space that meets the need for identification and that the transformation of prowess into an identity form. Also, different identification views of being a supporter/fan of a football team reflected in the advocacy practices in daily life, and the phenomenon of fanaticism which is caused by mass / group feeling in public places in the stadium and outside was examined.